2013
DOI: 10.1111/febs.12574
|View full text |Cite|
|
Sign up to set email alerts
|

Curcumin up‐regulates phosphatase and tensin homologue deleted on chromosome 10 through microRNA‐mediated control of DNA methylation – a novel mechanism suppressing liver fibrosis

Abstract: Phosphatase and tensin homologue deleted on chromosome 10 (PTEN) has been reported to play a role in the suppression of activated hepatic stellate cells (HSCs). Moreover, it has been demonstrated that hypermethylation of the PTEN promoter is responsible for the loss of PTEN expression during HSC activation. Methylation is now established as a fundamental regulator of gene transcription. MicroRNAs (miRNAs), which can control gene expression by binding to their target genes for degradation and/or translational r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(82 citation statements)
references
References 32 publications
6
75
0
Order By: Relevance
“…10 The miR-29 family consists of miR-29a, miR-29b, and miR-29c, which differ only in two or three bases. 24,25 Recent studies showed that DNMTs may be a target of miR-29 family.…”
Section: Mir-29b Regulates Pten Expression By Targeting Dnmt3b and Ismentioning
confidence: 99%
See 1 more Smart Citation
“…10 The miR-29 family consists of miR-29a, miR-29b, and miR-29c, which differ only in two or three bases. 24,25 Recent studies showed that DNMTs may be a target of miR-29 family.…”
Section: Mir-29b Regulates Pten Expression By Targeting Dnmt3b and Ismentioning
confidence: 99%
“…3 Our previous study found that curcumin upregulates miR-29b expression, leading to the silencing of DNA methyltransferase 3b (DNMT3b) and the loss of phosphatase and tensin homolog deleted on chromosome 10 (PTEN) methylation, which contributes to suppression of activated HSCs. 10 Other ncRNAs, such as long intergenic non-coding RNAs (lincRNAs) and the heterogeneous group of long non-coding RNAs (lncRNAs), have also been reported to be involved in human diseases. [11][12][13] LncRNA is most commonly defined as a non-protein-coding RNA molecule longer than 200 nucleotides.…”
Section: Introductionmentioning
confidence: 99%
“…33 However, our group identified only DNMT3b as a target of miR-29b in rat HSCs. 34 Therefore, the targets of miRNAs may vary in different tissues, and should be determined using confirmatory analyses, such as the dual luciferase reporter experiment. Here, Smad7 was predicted as a target of miR-17-5p, which was confirmed with the dual luciferase reporter experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Primers for alpha-1 (I) collagen (Col1A1), α-SMA, GAPDH and U6 were designed as described previously. 18 To detect miR-17-5p and miR-238 expression, the RT reaction was performed using the TaqMan MicroRNA Assay (Applied Biosystems, Foster City, CA) according to the manufacturer's instructions. GAPDH and U6 snRNA (Applied Biosystems, Foster City, CA) levels were measured and used to normalize the relative abundance of mRNA and miRNA, respectively.…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation